English Material Instruction in National Curriculum - Aip Syaepul Uyun (UIN Sunan Gunung Djati Bandung, 2023)
This paper aims to analyze the scope of material instruction provided by the merdeka curriculum, and its compatibility to student needs. The research used qualitative descriptive method with interview and document analysis to collect the data. The research found that the material scope of English in merdeka curruculum never change significantly at least starting from 2004 curriculum. There are some added and taken away, but the essence of the material still remains the same. English material for junior and sinior high school students can be divided into three major parts. The firts is English expression such as introduction, gratitude, apolozy, ability and disability, like and dislike, agreement, posibility, warning and asking giving expression. The second is short functional text such as writing short message, announcement, advertisement, and greeting card. The last one is essay funtional text such as narrative, descriptive, recount, report and procedural text. Meanwhile, the data also shows that the priority skills needed by schools and students are writing and speaking. Therefore, teachers in this case, with the authority they have, can develop the curriculum according to needs. What the school does is use a skills approach, where all material is taught with an orientation towards speaking and writing skills. so that even if the material provided by the curriculum does not directly suit the needs of students and schools, they can still adapt to their needs.